Pengembangan Video Pembelajaran Sparkol Videoscribe dengan Model Pembelajaran Make A Match pada Materi Lingkaran di MTS Alkhairaat - Fitrianti Fitrianti (SUPERMAT : Jurnal Pendidikan Matematika, 2022)
This research is a development research that focuses on developing mathematics learning videos. This research was conducted at MTS Alkhairaat in class VIII. The results of this study, based on the make a match-based sparkol videoscribe learning video, obtained an average score of 3.79 with "valid" criteria from the assessment of material experts and obtained an average score of 3.84 with "valid" criteria from the assessment of media experts. Then the results of the product attractiveness test that were tested on students in class VIII MTS Alkhairaat which were grouped into small groups consisting of 10 students obtained an average value of 3.5 "very interesting" criteria and the results of the large group trial consisting of of 20 people obtained an average result of 3.69 with the criteria of "very interesting".